MONTECINO, LÉSMER (ed.) (2010). Discurso, pobreza y exclusión en América Latina - Berardi, Leda (Revista Latinoamericana de Estudios del Discurso, 2020)
MONTECINO, LÉSMER (ed.) (2010). Discurso, pobreza y exclusión en América Latina. Santiago: Ed. Cuarto Propio, 364pp. ISBN 978-956-260-515-1.